Diversity and development of glandular trichomes in Lomatozona artemisiifolia Baker (Asteraceae - Eupatorieae) - Trindade, Luma Mota Palmeira (2014)
an endemic plant species from the Cerrado of Goiás. Lomatozona artemisiifolia is found only in the State of Goiás, Brazil. In this study we identifi ed glandular trichomes on aerial vegetative organs and fl owers, and described the main ontogenetic stages of trichomes in leaves and stems. Samples of stems, leaves, fl owers, and involucral bracts were analyzed under optical and scanning electron microscopy. L. artemisiifolia has glandular trichomes, classifi ed into four types. Type I has a uniseriate peduncle and biseriate head; type II is biseriate peduncular; type III is biseriate with a vesicular aspect; and type IV is uniseriate and curved towards the epidermis, with a long peduncle and unicellular head. The initial event in trichome development is the expansion of the protodermal cell. In trichomes with uniseriate peduncles, the fi rst division is periclinal. In biseriate trichomes, it is anticlinal. These results contribute to the knowledge on the genus and may support taxonomic studies of the tribe.